Making simple robots - Ceceri, Kathy, ....- (Sebastopol : Maker Media, 2015)
Making Simple Robots is based on one idea: Anybody can build a robot! That includes kids, school teachers, parents, and non-engineers. If you can knit, sew, or fold a flat piece of paper into a box, you can build a no-tech robotic part. If you can use a hot glue gun, you can learn to solder basic electronics into a low-tech robot that reacts to its environment. And if you can figure out how to use the apps on your smart phone, you can learn enough programming to communicate with a simple robot. Written in language that non-engineers can understand, Making Simple Robots helps beginners move beyond basic craft skills and materials to the latest products and tools being used by artists and inventors. Find out how to animate folded paper origami, design a versatile robot wheel-leg for 3D printing, or program a rag doll to blink its cyborg eye. Each project includes step-by-step directions as well as clear diagrams and photographs. And every chapter offers suggestions for modifying and expanding the projects, so that you can return to the projects again and again as your skill set grows.
Includes index.
Keywords: Robots -- Design and construction -- Amateurs' manuals